Governance fragmentation and food security in South Africa’s Upper Umzimvubu River catchment: A network governance perspective - Betty Claire Mubangizi (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2027)
The Upper uMzimvubu River catchment in South Africa’s Eastern Cape faces persistently low food productivity, driven by land degradation and the escalating impacts of climate change. This study investigates how governance dynamics shape food security outcomes on rural communal land, focusing on the potential of collaborative, multi-level, and networked governance approaches to address systemic vulnerabilities and enhance local food production. Using a review-based methodology grounded in both empirical insights and scholarly literature on food governance, the research applies a network governance framework to examine how state and non-state actors coordinate interventions in the food security landscape. The findings indicate that food insecurity in the catchment arises not only from environmental and socio-economic stressors but is also exacerbated by fragmented governance, policy incoherence, and institutional weaknesses. In this context, civil society networks play a central role in polycentric governance, often bridging gaps left by formal institutions. The study advocates a decentralised, participatory, and integrated model of food security governance, emphasising secure land tenure, climate-resilient development planning, and improved coordination among diverse stakeholders. By integrating perspectives from environmental governance, rural development, and land tenure studies, this research provides a transdisciplinary lens on food insecurity. It demonstrates how combining policy analysis, local knowledge, and institutional theory can foster collaboration among academics, policymakers, and civil society actors, ultimately enabling more effective responses to the complex challenges of rural food insecurity in South Africa.